2022
DOI: 10.1111/jipb.13390
|View full text |Cite
|
Sign up to set email alerts
|

A bZIP transcription factor (CiFD) regulates drought‐ and low‐temperature‐induced flowering by alternative splicing in citrus

Abstract: Drought and low temperature are two key environmental factors that induce adult citrus flowering. However, the underlying regulation mechanism is poorly understood. The bZIP transcription factor FD is a key component of the florigen activation complex (FAC) which is composed of FLOWERING LOCUS T (FT), FD, and 14-3-3 proteins. In this study, isolation and characterization of CiFD in citrus found that there was alternative splicing (AS) of CiFD, forming two different proteins (CiFDα and CiFDβ). Further investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 80 publications
(125 reference statements)
2
3
0
Order By: Relevance
“…The two transcripts of CiFD (CiFDα and CiFDβ) in citrus involved in drought and low temperature induced owering exhibited similar expression patterns in different tissues. However, they differed in terms of subcellular localization and transcriptional activity (Ye et al 2023), which is consistent with the ndings of this experiment. In this study, we found that the two transcripts of SiAAP9 showed consistent expression patterns in different tissues of Jingu 21, as well as in response to NO 3 induction and NO 3 starvation (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…The two transcripts of CiFD (CiFDα and CiFDβ) in citrus involved in drought and low temperature induced owering exhibited similar expression patterns in different tissues. However, they differed in terms of subcellular localization and transcriptional activity (Ye et al 2023), which is consistent with the ndings of this experiment. In this study, we found that the two transcripts of SiAAP9 showed consistent expression patterns in different tissues of Jingu 21, as well as in response to NO 3 induction and NO 3 starvation (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, TaGS3 produces five splice variants, with TaGS3.5 significantly increasing grain weight upon overexpression, while TaGS3.1 has the opposite effect [59]. The citrus CiFD gene has two transcripts, CiFDα and CiFDβ, involved in the flowering response to drought and low temperature, showing similar expression patterns across various tissues but differing in subcellular localization and transcriptional activity [60], aligning with the results of this experiment. Our study reveals consistent expression patterns of the two transcripts of Si-AAP9 in different tissues of Jingu 21, as well as in response to NO3 -induction and starvation conditions (Figure 2).…”
Section: Two Transcripts Of Siaap9 Perform Identical Functions But Ex...supporting
confidence: 82%
“…64 CibHLH96 binds to the CiFD promoter and activates its expression to regulate drought-induced flowering in citrus. [70][71][72]74,76,77,79 In Zoysia japonica, ZjICE1/2 directly binds to the MYC motifs in the promoter of ZjDREB1, resulting in elevated expression and increased drought stress tolerance. 166,213 In rice, OsbHLH057 binds to the AATCA cis-element of the Os2H16 promoter and then promotes its expression.…”
Section: The Function Of Bhlh Transcription Factors In Abiotic Stress...mentioning
confidence: 99%
“…Similarly, CabHLH10 specifically binds to the G-box elements in the promoter of CaRD22 , a dehydration- and ABA-responsive gene, and then enhances its expression to confer ABA-dependent drought tolerance as well as enhance yield/productivity in Cicer arietinum . CibHLH96 binds to the CiFD promoter and activates its expression to regulate drought-induced flowering in citrus. ,,,, In Zoysia japonica , ZjICE1/2 directly binds to the MYC motifs in the promoter of ZjDREB1 , resulting in elevated expression and increased drought stress tolerance. , In rice, OsbHLH057 binds to the AATCA cis -element of the Os2H16 promoter and then promotes its expression . Additionally, Chander et al reported that OsICE1 overexpression plants was able to improve photosynthetic performance and reduce grain loss in rice plants under severe drought conditions. , PebHLH35 involved in the regulation of drought tolerance through activating the expression of PeGSTU58 .…”
Section: The Function Of Bhlh Transcription Factors In Abiotic Stress...mentioning
confidence: 99%